2018
DOI: 10.1007/s10029-018-1817-x
|View full text |Cite|
|
Sign up to set email alerts
|

Causes of recurrence in laparoscopic inguinal hernia repair

Abstract: Recurrence can occur at any stage following inguinal hernia surgery. Patients' risk factors such as higher BMI, smoking, diabetes and postoperative surgical site infections increase the risk of recurrence and can be modified. Amongst the surgical factors, surgeon's experience, larger mesh with better tissue overlap and careful surgical techniques to reduce the incidence of seroma or hematoma help reduce the recurrence rate. Other factors including type of mesh and fixation of mesh have not shown any difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 93 publications
2
37
0
Order By: Relevance
“…Recurrences after inguinal hernia repairs can occur even up to 50 years later [2]. In recent administrative data and registry analyses it was revealed that the proportion of recurrent repairs in the total collective of inguinal hernia repairs among men was 11.3-14.3% [3][4][5][6][7] and in women 7.0-7.4% [4,8]. By contrast, in systematic reviews and meta-analyses the recurrence rates were still far lower (1.2-3%) than those cited above since the included studies had a maximum follow-up time of 6 years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrences after inguinal hernia repairs can occur even up to 50 years later [2]. In recent administrative data and registry analyses it was revealed that the proportion of recurrent repairs in the total collective of inguinal hernia repairs among men was 11.3-14.3% [3][4][5][6][7] and in women 7.0-7.4% [4,8]. By contrast, in systematic reviews and meta-analyses the recurrence rates were still far lower (1.2-3%) than those cited above since the included studies had a maximum follow-up time of 6 years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surgical procedures are available to treat groin hernias. [27][28][29][30][31] The technique selection depends on the surgeons' expertise and preference, patient-and herniarelated characteristics, and local resources available. 1,2 The international guidelines for management of groin hernias (HerniaSurge Group) suggest that laparoscopic repair is an optimal technique that is associated with faster recovery time, lower chronic pain, lower risk, and are costeffective.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to TAPP, TEP has the advantage of not entering the peritoneal cavity and therefore reducing abdominal viscera lesions, especially in patients with intra-abdominal adherence. 15,26,29 However, some surgeons avoid or contraindicate the TEP and even the TAPP approach in patients with previous lower abdominal operations because of the difficulty to dissect the preperitoneal space and prevent intra-abdominal organ injuries. 13,15 Intra-abdominal adherence and abdominal wall fibrosis secondary to prior abdominal operations increase operative time, conversion to open surgery, complication rate, and hospital stay and costs in patients subjects to either open or laparoscopic abdominal operations.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggests that single incision laparoscopic surgery has a higher incidence of port-site hernia when compared to conventional laparoscopy. 54 Studies have also shown a higher incidence of port-site hernia in cases of single incision robotic procedures. 55 With the multitude of port entry and closure techniques, it will be an uphill task for the surgeon to familiarize with all the techniques.…”
Section: Whether To Close or Notmentioning
confidence: 99%